2015
DOI: 10.4103/2394-5079.167378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural compounds in treatment and prevention of hepatotoxicity and hepatocellular carcinoma

Abstract: Liver diseases are most common disorders in the world and characterized by rapid changes from steatosis to chronic hepatitis, fi brosis, cirrhosis, and hepatocellular carcinoma (HCC). Natural products that attained great attention is to be used in the prevention and treatment of multiple diseases in humans. Several researches have been reported numerous natural and phytochemical compounds that may counteract or prevent the hepatic injury and primary liver cancer. The conservative treatment of liver toxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Thus, under the conditions of analysis established, ginkgo without additives were neither cytotoxic nor genotoxic. The results of nontoxic action at the cellular level of ginkgo without industrialization obtained in the present study corroborate the results of non-cytotoxicity and nongenotoxicity of this plant found in the scientific literature, including the studies of Turkez et al (2014), Hamzawy et al (2015) and Oliveira et al (2017). Table 1.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, under the conditions of analysis established, ginkgo without additives were neither cytotoxic nor genotoxic. The results of nontoxic action at the cellular level of ginkgo without industrialization obtained in the present study corroborate the results of non-cytotoxicity and nongenotoxicity of this plant found in the scientific literature, including the studies of Turkez et al (2014), Hamzawy et al (2015) and Oliveira et al (2017). Table 1.…”
Section: Resultssupporting
confidence: 92%
“…Leaves of Ginkgo biloba L. (Family Ginkgoaceae), a species native to Eastern countries, such as China and Japan, have long been used for the treatment and prevention of cardiopulmonary dysfunctions, labyrinthitis and diseases triggered by senescence (POLANSKI et al, 2016;MAHMOUDIAN-SANI et al, 2017). This plant also has recognized antioxidant potential (HAMZAWY et al, 2015). It is popularly known as ginkgo or maidenhair tree, and has high concentrations of ginkgolide diterpenes, bilobalide sesquiterpenes, triterpenes, polyphenols, ginkgolide acids, flavones, flavonols and biflavonoids in the foliage (POLANSKI et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the experiment, all the environmental conditions were the same for the treatments, receiving food and water, ad 6) Positive control + 10 g/kg diet of SMS + 10 g/kg diet of TV + 5 g/kg diet of RO as blend of herbs (BH). The selection of aflatoxin B1 and herbs doses employed in this experiment was based on previous studies (Zhao et al, 2010;Chand et al, 2011;Hamzawy et al, 2012). The herbs utilized in the experiment were freshly harvested (whole aerial organs of RO and TV and the seeds of SMS), and dried, added to the diet as additive.…”
Section: Birds and Experimental Designmentioning
confidence: 99%
“…It is effective as anthelmintic, antispasmodic, carminative, sedative, diaphoretic, antimicrobial, antioxidant, and antifungal agents because its contents of essential oils and anti-oxidative phenolic compounds [geraniol (G), α-terpineol (A), thuyanol-4 (U), linalool (L), carvacrol (C), and thymol (T)]. [131,132] The volatile oils of thyme has been shown to exhibit anti-microbial, anti-mutagenic, anti-platelet, analgesic, anti-inflammatory, anti-angiogenic, anti-oxidant, anti-elastase, insecticidal, anti-parasitic, cell-protective, and anti-tumor activity. [133,134] Recently, the various studies showed that the beneficial effects of thyme was based on the activation of the apoptosis response, including reduction in mitochondrial membrane capacity and Bcl-2/Bax ratio as well as elevation in cytochrome release from mitochondria and caspase activity.…”
Section: Milk Thistlementioning
confidence: 99%